2007
DOI: 10.1016/j.jns.2007.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood perfusion changes in multiple sclerosis

Abstract: | The proximity of immune cell aggregations to the vasculature is a hallmark of multiple sclerosis. Furthermore, it is widely accepted that inflammation is able to modulate the microcirculation. Until recently, the detection of cerebral blood perfusion changes was technically challenging, and perfusion studies in multiple sclerosis patients yielded contradictory results. However, new developments in fast magnetic resonance imaging have enabled us to image the cerebral hemodynamics based on the dynamic tracking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 54 publications
1
30
1
Order By: Relevance
“…Veins are typically considered capacitance vessels, and although they can constrict or dilate passively, their luminal size can also be modulated by a variety of mechanisms. For example, sympathetic activity can constrict veins, 26 and abnormal autonomic function can therefore result in venous dilatation in diseases where autonomic function is altered, such as MS. 27 In addition, the relationship between enlarged veins and impaired cerebral arterial blood flow, which has been described in several studies in MS, [28][29][30] may require consideration. It is worth noting that medullary veins in the brain can dilate in the setting of acute ischemia, 31 and cerebrovascular reactivity can be modulated by changes in the fraction of inspired carbon dioxide, 32 but whether such mechanisms play a role in MS is unknown.…”
Section: Ms Vs Non-ms Veinsmentioning
confidence: 99%
“…Veins are typically considered capacitance vessels, and although they can constrict or dilate passively, their luminal size can also be modulated by a variety of mechanisms. For example, sympathetic activity can constrict veins, 26 and abnormal autonomic function can therefore result in venous dilatation in diseases where autonomic function is altered, such as MS. 27 In addition, the relationship between enlarged veins and impaired cerebral arterial blood flow, which has been described in several studies in MS, [28][29][30] may require consideration. It is worth noting that medullary veins in the brain can dilate in the setting of acute ischemia, 31 and cerebrovascular reactivity can be modulated by changes in the fraction of inspired carbon dioxide, 32 but whether such mechanisms play a role in MS is unknown.…”
Section: Ms Vs Non-ms Veinsmentioning
confidence: 99%
“…Focal perfusion abnormalities are typically observed in and around contusions, even before they become apparent on structural imaging (63)(64)(65). Perfusion, measured using Xenon-enhanced computed tomography (Xe-CT) (80)(81)(82)(83), CTP (63), and DSC-MRI (82)(83)(84), are altered in peri-contusional edematous regions, suggesting ongoing ischemic damage, and a role for perfusion imaging in prognosis (63,85). Focal brain perfusion abnormalities associated with extra-axial blood collections correlate with symptomatology.…”
Section: Conventional Mri Techniquesmentioning
confidence: 99%
“…This hypothesis is further supported by a quantitative MRI study that reported significantly increased venous oxygenation levels and decreased cerebral metabolic rates of oxygen in MS patients as compared with healthy controls [18]. Furthermore, vascular damage, a sequel of (perivascular) inflammation and gliosis [19] in MS, is associated with a globally reduced cerebral perfusion [20] and may thus contribute to diminished venous visibility on T2*w images [14,15]. Another possible cause of decreased oxygen uptake is the high level of nitric oxide (NO) due to repetitive vascular inflammation in MS competitively inhibiting mitochondrial uptake of oxygen in MS [18].…”
Section: Discussionmentioning
confidence: 75%